2020
DOI: 10.21203/rs.3.rs-21674/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology and risk factors of rectal colonization of carbapenemase-producing Enterobacteriaceae among high-risk patients from ICU and HSCT wards in a university hospital

Abstract: Background: Nosocomial infections caused by carbapenemase-producing Enterobacterieceae (CPE) constitute a major global health concern and are associated with increased morbidity and mortality. Rectal colonization with CPE is a risk factor for bacterial translocation leading to subsequent endogenous CPE infections. This prospective observational study was aimed to investigate the prevalence and epidemiology of rectal colonization of CPE, the carbapenemase genotypes, and to identify the independent risk factors … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…In this study, the collection site varied according to the pathogen tested ( Table 2 ). Our data corroborate the fact that rectal swabs were more sensitive than fecal cultures 20 , 21 , especially regarding VRE and CRE. Despite this, rectal swabs should be used with care in patients undergoing HSCT to prevent skin or mucosal injuries during severe neutropenia.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the collection site varied according to the pathogen tested ( Table 2 ). Our data corroborate the fact that rectal swabs were more sensitive than fecal cultures 20 , 21 , especially regarding VRE and CRE. Despite this, rectal swabs should be used with care in patients undergoing HSCT to prevent skin or mucosal injuries during severe neutropenia.…”
Section: Discussionsupporting
confidence: 88%
“…Our data corroborate the fact that the rectal swab is more sensitive than the culture of feces [18,19], especially regarding VRE and CRE. Despite this, the use of rectal swab in HSCT patients should be used with care, to avoid skin or mucosal breakdown during severe neutropenia.…”
Section: Discussionsupporting
confidence: 87%
“…A study comprising active screening of CRE infections in hematology units in China reported that the CRE colonization rate in patients was 16.46% [27]. In a prospective cohort study of inpatients from the ICU and hematopoietic stem cell transplantation wards, the CRE colonization rate was 16.67% and KPC-producing K. pneumoniae was dominant [28]. National surveillance of CRE strains in China showed that KPC-2 and NDM were responsible for phenotypic resistance in 90% of CRE strains [29].…”
Section: Epidemiology Of Crementioning
confidence: 99%